Politics of desire: exploring the ethnicity/sexuality intersectionality in south asian and east asian men who have sex with men (MSM) - das Nair, Roshan; Thomas, Shirley A. (British Psychological Society, 2012)
Intersectionality’ has been used to interrupt dominant discourse surrounding LGB experiences, and has exposed their heterogeneity. Complexities of negotiating desire within a matrix of race/ethnicity and sexuality in South and East Asian men who have sex with men (MSM) has been under-explored in Black and Minority Ethnic LGB research. Our internet survey found discordance between sexual identities and sexual practices amongst Asian MSM. Many did not access LGB physical and cyberspaces, and some experienced abuse attributed to their race/ethnicity. Feeling undesired was read as a function of racism, but racism from Asian MSM, manifesting as dispreference for certain races/ethnicities, was also found. We also explored intersections between internalised racism and homophobia which affect the lived experience of diasporic Asian MSM.